Effective Privacy Preserving in Networks Using Merkle Hash Trees - Sunitha, A; reddy, K Sudha (IJRDO -Journal of Computer Science Engineering, 2015)
The design of two-tiered sensing element networks,wherever storage nodes function Associate in performing intermediatetier between sensors and a sink for storing knowledge and processqueries, has been wide adopted thanks to the advantages of power andstorage saving for sensors yet because the potency of question process.However, the importance of storage nodes conjointly makes thementicing to attackers during this paper, we have a tendency to proposeSafeQ, a protocol that forestalls attackers from gaining info from eachsensing element collected knowledge and sink issued queries. SafeQconjointly permits a sink to observe compromised storage nodes afterthey act. To preserve privacy, SafeQ uses a unique technique tocypher each knowledge and queries such a storage node will properlymethod encoded queries over encoded knowledge while not knowingtheir values. To preserve integrity, we have a tendency to propose 2schemes—one victimization Merkle hash trees and another employinga new system referred to as neighborhood chains—to generateintegrity verification info so a sink will use this info to verify whetheror not the results of a question contains precisely the knowledgethings that satisfy the query to boost performance, we have a tendencyto propose Associate in Nursing optimization technique victimizationBloom filters to scale back the communication price between sensorsand storage nodes